Social distribution of cardiovascular disease risk factors: change among men in England 1984–1993. Issue 11 (1st November 2000) - Bartley, M; Fitzpatrick, R; Firth, D; Marmot, M
Abstract : OBJECTIVE: To investigate change in the social distribution of some of the main risk factors for cardiovascular disease in men in England during a period when inequality in cardiovascular disease mortality widened DESIGN: Age standardised comparison of the social distribution of seven known risk factors for cardiovascular disease (body mass index, waist to hip ratio, systolic and diastolic blood pressure, consumption of fresh green vegetables, leisure time exercise, cigarette smoking and levels of social support) in two large cross sectional representative samples of the English population. SUBJECTS: Men aged 20–64 years in the 1984 Health and Lifestyle Survey (excluding Scotland and Wales) first sweep and the 1993 Health Survey for England. MAIN OUTCOME MEASURES: Mean values of continuous variables; age adjusted proportions of categorical variables; change in the relative index of inequality for each risk factor. RESULTS: The overall prevalence of cardiovascular disease risk factors improved during the period in which cardiovascular disease mortality was falling. The social distribution of cardiovascular disease risk factors, in contrast, did not become more extreme. Increases in the relative index of inequality for angina from 1.75 to 1.86, for eating vegetables less than once a day from 1.76 in 1984 to 1.96 in 1993, and an apparently larger increase in inequality of social support, from 1.92 to 2.53 were not statistically significant. In most cases the degree of inequality in risk factors tended to narrow non-significantly: for example the relative index of inequality fell from 5.02 in 1984 to 3.07 in 1993 for systolic blood pressure, from 5.60 to 4.29 for current smoking and from 6.24 to 4.19 for eating other than wholemeal bread as the main form of bread in the diet. The two statistically significant changes in inequality were in the direction of narrowing inequality: from a relative index of inequality of 2.12 to 0.90 for diastolic blood pressure (p<0.01) and from 19.3 to 0.87 (p<0.01) for psychological distress as indicated by the General Health Questionnaire. CONCLUSIONS: Healthier lifestyle options have not been adopted at a significantly faster rate by middle class than working class people over this time period. At the population level the change in risk factors is consistent with falling cardiovascular mortality. The change in the social distribution of risk factors within the population, however, shows little or no relation to the pattern of widening inequality in cardiovascular mortality. This may be because the effect is lagged, or because the adoption of healthier behaviour confers greater benefits on those in higher socioeconomic status groups.